2001
DOI: 10.1002/1097-4636(20011205)57:3<366::aid-jbm1179>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Manipulation of selective cell adhesion and growth by surface charges of electrically polarized hydroxyapatite

Abstract: Adherence of cells to a surface, such as a biomaterial surface, can be significantly influenced by the surface charge on that material. The applicability of electrically charged hydroxyapatite ceramics to selective cell adhesion was examined, and we show that polarized hydroxyapatite has significant effects on cell growth and adhesion. The surface charge applied to polarized hydroxyapatite promotes (i) enhanced colony formation of osteoblast-like cells, (ii) activation of gap junctions, and (iii) specific orie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
128
2
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(147 citation statements)
references
References 24 publications
9
128
2
2
Order By: Relevance
“…On the contrary, they reasoned that the adsorption of negative anions on positively polarized surfaces acted as antiadhesive cues, minimizing cell adhesion. 16 The importance of surface charge has also been put forward in the design of nanoparticles (NPs) for cell internalization purposes (e.g. drug delivery or gene therapy).…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the contrary, they reasoned that the adsorption of negative anions on positively polarized surfaces acted as antiadhesive cues, minimizing cell adhesion. 16 The importance of surface charge has also been put forward in the design of nanoparticles (NPs) for cell internalization purposes (e.g. drug delivery or gene therapy).…”
Section: Introductionsupporting
confidence: 89%
“…[14][15][16] It is believed that the surface charges built by polarization encourage ion and protein binding of essential constituents on the surface of the biomaterial needed for cell attachment and growth. 16 Ohgaki et al justified an observed greater cell growth on negatively polarized surfaces by the adsorption of Ca and the subsequent attraction of cell adhesion proteins, such as integrins, fibronectin, and osteonectin, which show divalent cation-dependent ligand binding. Upon anchoring of cell adhesion proteins, cell adhesion would follow.…”
Section: Introductionmentioning
confidence: 99%
“…However, recently there has been increasing evidence that the biological response is also affected by the physical properties of the material (4). In particular, it has been demonstrated that cells are influenced by the substrate topography (5, 6), rigidity (7,8), anisotropy (9, 10), surface charge (11,12), and wettability (13,14). From this perspective, cellular response to external stimuli goes far beyond the bare ability of the cell to chemically sense specific ECM ligands and includes a wide range of physical cues that are generated at, or act on, the interface between cells and the surrounding environment.…”
mentioning
confidence: 99%
“…While the link between charge and cellular interactions is not well understood, previous studies investigating cellular adhesion and growth on poled hydroxyapatite suggest that surface charge influences cellular response. 11 The piezoelectric properties of collagen type I have been studied at scales ranging from the macroscale 1 to, more recently, the nanoscale 12 with the advent of piezoresponse force microscopy (PFM). 13,14 Collagen type I is a shear piezoelectric with a polarization along the fibril length (corresponding to an amine (N) to carboxyl (C) polarity).…”
Section: Introductionmentioning
confidence: 57%